Murder on a summer's day - Brody, Frances (Brody, Frances. Kate Shackleton mystery., 2016)
"When the India Office seek help in finding Maharajah Narayan, last seen hunting on the Bolton Abbey estate, they call upon the expertise of renowned amateur detective Kate Shackleton to investigate. But soon a missing persons case turns to murder. Shot through the heart, Narayan's body has obviously not been in the woods overnight. Who brought it here, and from where? And what has happened to the hugely valuable diamond that was in the Maharajah's possession? An inexplicable murder ... As Kate digs deeper, she soon discovers that vengeance takes many forms. Was the Maharajah's sacrilegious act of shooting a white doe to blame? Or are growing rumors of a political motive too powerful for Kate to discount? One thing Kate is sure of: her own skills and insights. Qualities that she is sure will help her unravel a mysterious murder on that fateful summer's day"--